The Effect of Group Counseling Based on Health Belief Model on Nutritional Behavior of Pregnant Women with Overweight: a Randomized Controlled Trial - Sahar Saadatnia; Farzaneh Soltani; Amir Saber; Farideh Kazemi (Hamadan University of Medical Sciences, 2021)
Introduction: Overweight and obesity are a significant challenge in pregnancy care. This study was conducted to investigate the effect of group counseling based on health belief model on nutritional behavior of overweight pregnant women referred to Kermanshah health centers. Methods: This clinical trial was performed in 2018 on 90 pregnant women in Kermanshah. Among the comprehensive health centers, 4 centers were randomly selected for intervention and 4 centers for the control group. Then 4 sessions of group counseling program prepared for the intervention groups were performed for one month. The content of the counseling included nutrition counseling and familiarity with the food pyramid and principles of proper nutrition, increasing sensitivity to obesity and its complications, understanding the severity of the obesity problem, understanding the obstacles and benefits of following a proper diet and increasing self-efficacy and ultimately achieving healthy eating behavior. The data collection tool was a researcher-made questionnaire including demographic and midwifery information, health belief model constructs, knowledge and nutritional behavior questionnaire. Data were analyzed using SPSS 16. Significance level was considered less than 0.05. Findings: The mean age of participants in the intervention group was 24.91(6.19) and in the control group was 27.53(5.60). After controlling the effect of pre-test scores on the constructs of knowledge, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy and nutritional behavior, the results showed a significant increase after the intervention, in the mean scores of the intervention group (P=0.001). Conclusion: The findings of this study showed the effectiveness of counseling based on the health belief model in promoting the nutritional behavior of pregnant women with high body mass index. Researchers in this study recommend counseling interventions based on this model. Therefore, the implementation of counseling intervention based on the structures of the health belief model can play an effective role in improving the nutritional behavior patterns of pregnant women.